The quality of women’s life after breast carcinoma surgery - Kulesza-Brończyk, Bożena; Terlikowski, Robert; Dobrzycka, Bożena; Filipowska, Joanna; Półjanowicz, Wiesław; Lejmanowicz, Krzysztof (Polish Journal of Public Health, 2009)
Introduction. Breast cancer is the major cause of death among women in Poland and its incidence shows a steady growing tendency. The diagnosis of breast cancer is a considerable psychological and physical burden. After surgery, the level of fear still increases, being strongly associated with posttraumatic stress.  Aim of the study. The study objective was to assess the quality of women’s life after breast carcinoma surgery.  Material and methods. The study was conducted in a group of 128 female members of the “Amazonki” clubs in Podlasie Province. The participants were divided into two groups according to surgery extent. The level of life quality was evaluated using standardized questionnaires: EORTC, QLQ-C30, QLQ-BR23 and FACT – B. Results. Breast carcinoma is accompanied by strongly negative emotional reactions, such as fear, irritability, hyperexcitability, the feeling of threat and anxiety. These symptoms were observed in both groups of patients. In the post-mastectomy group, the patients exhibited emotional lability, feeling of lost physical attraction, disturbed relationships and low self-esteem. Negative effects of fear and depression on the physical health as well as on the family and social life were also demonstrated. Only 8% of the study patients were interested in reconstructive surgery. Conclusions. The assessment of life satisfaction among women after mastectomy depends on the severity of posttraumatic stress. In the women who underwent tumorectomy, the quality of life is at a higher level. The female patients after mastectomy require long-term and complex specialist care that would help restore a sense of physical and emotional balance.